(untitled) (International Journal of Innovative Technologies in Economy, 2020)
The success or failure of the audit activities carried out by the auditor is known as audit quality. An audit is considered qualified if it is carried out in accordance with applicable auditing standards or regulations. There are several factors that can affect audit quality and one of them is emotional intelligence which will be the independent variable in this study. This study was conducted to test and analyze the influence of emotional intelligence on audit quality at the Public Accounting Firm in Bandung. The data used in this study are primary data obtained from distributing questionnaires to 48 partners of the Public Accounting Firm as respondents who participated in filling out the questionnaire. Data analysis in this study used a structural equation model - PLS. The results showed that emotional intelligence has a significant effect on audit quality.